Cyclopiazonic acid causes endothelium-dependent relaxation in rat aorta - Zheng Xiu-Feng; Guan Yong-Yuan; Kwan Chiu-Yin (Acta Pharmacologica Sinica, 2016)
The effects of cyclopiazonic acid (CPA), a selective inhibitor of Ca(2+)-pump ATPase for endoplasmic reticulum (ER), on the contractility of rat aorta with and without intact endothelium were studied to investigate the possible involvement of endothelial ER Ca(2+)-pump in the release of endothelium-derived relaxing factor (EDRF), which is known to cause vascular relaxation or inhibition of phenylephrine (PE)-precontracted aorta. When added to the organ bath cumulatively, CPA concentration-dependently caused gradual development of contraction, which was much less in aortic rings with intact endothelium than in endothelium-denuded aortic rings. But CPA at low concentrations (1-3 mumol.L-1) induced vascular relaxation when added to PE (3 mumol.L-1)-precontracted aortic rings with intact endothelium, but not in denuded aortic rings. This relaxant effect of CPA is very similar to the effect of acetylcholine (ACh), which is well recognized to be mediated by the release of EDRF from the endothelium. NG-nitro-L-arginine methyl ester (L-NAME), a nitric oxide synthase inhibitor, completely prevented the vascular relaxation induced by CPA or ACh and the inhibitory effect of L-NAME was partially reversed by L-arginine (L-Arg). Treatment of the aortic rings with nifedipine (Nif) 0.3 mumol.L-1 did not affect the relaxant effect of ACh or CPA on PE-induced contraction indicating that the Ca(2+)-entry to the endothelial cells as a result of receptor activation by ACh or ER Ca(2+)-pump inhibition by CPA was via channels other than L-type Ca2+ channels.